Freedom of Expression in South Sudanese Judicial Struggle: Bought or Fought For? With Special Reference to India - Varun Chhachhar; Wol Deng Akech (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
This article examines the struggle of the South Sudanese people in the courtroom for freedom of expression with special reference to India. The aim is thus to illustrate the judicial perspective on interpretation of this fundamental right from the past to the present. This evaluation in nexus to the contemporary constitutional adjudication in the world at large and South Sudan in particular tries to draw the attention of the courts in South Sudan to adopt a progressive interpretation. It also stresses focus on interpretation adopted by judges in South Sudan. The paper seeks to reckon the concerned institutions in South Sudan to the ongoing liberal jurisprudences on the right to freedom of speech and expression on one hand and on the other hand informs the concerned institutions for a serious litigation and enforcement of Bill of Rights in South Sudan. Indeed, the paper has invoked progressive interpretations of fundamental rights from the U.K, India, and the U.S to help in justifying the grounds as to why South Sudanese litigants and courts should scarcely claim and upheld freedom of expression as fundamental and foundational tenet of a democratic society. The article concludes that the sanctity of all rights will be meaningless if freedom of expression is not accorded an important status by the concerned institutions.